Shadow of my shadow - Doyle, Jennifer (Feminist studies, 2024)
"Shadow of My Shadow is a personal and theoretical account of sexualized harassment and its reverberations within institutional bureaucracies. Jennifer Doyle's own experience of being stalked at work serves as the basis for an extended meditation on how harassment profoundly reshaped her relationship to work, to writing, and ultimately to herself. In the first chapters, Doyle explores how the act of writing about being a harassed subject often amplifies the very stigma that the victim wishes to dispel. Her reflections expose the ways that harassment occurs at the very junctures where work and life and the personal and the public meet. From there, Doyle theorizes the Larry Nassar case and Elena Ferrante's Neopolitan novels, enacting close, almost obsessive textual analysis as an act of self-erasure. Shadow of My Shadow not only expands our understanding of harassment ecologies across the personal, the archival, and the literary, it models ethical thinking about how to represent sexual violence"--